Methods of Market Approach in business valuation in the Czech conditions - Krch, Přemysl; Mařík, Miloš, 1947-; Jahodová, Lucie; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2010)
The purpose of the diploma thesis was to assess the applicability of Market Approach in business valuation of the Czech entities. The first part comprises basic description of Valuation methods, the core of the thesis describes the guideline publicly traded companies method - multiples, comparable companies etc. -, guideline transaction method and industry multiples method. The application part consists of two valuations using guideline publicly traded companies method - the valuation of Komercni banka and of Trinecke zelezarny.
Vedoucí práce: Miloš Mařík
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2010
Rok obhajoby 2010
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses